2015
DOI: 10.1016/j.ymgmr.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Catel–Manzke syndrome: Further delineation of the phenotype associated with pathogenic variants in TGDS

Abstract: Catel-Manzke syndrome is a rare autosomal recessive disorder characterized by Pierre Robin sequence with hyperphalangy and clinodactyly of the index finger. Recently, homozygous or compound heterozygous pathogenic variants in TGDS have been discovered to cause Catel-Manzke syndrome. Here, we describe a 12-month-old male with molecularly confirmed Catel-Manzke syndrome who presented with Pierre Robin sequence (but without cleft palate) and hyperphalangy, and we compare his phenotype with the seven previously de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Individual 1 is homozygous for the variant c.700T>C, p.(Tyr234His), which has been reported in compound heterozygous state in another Dutch family (Ehmke et al, ; Kant et al, ). She presented with retrognathia and cleft palate, and her facial appearance is similar to the Individual 2 reported by Ehmke et al () and the individual reported by Pferdehirt et al (). Individual 2 in this report carries the above mentioned variant c.700T>C, p.(Tyr234His) and the most common variant c.298G>A, p.(Ala100Ser).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Individual 1 is homozygous for the variant c.700T>C, p.(Tyr234His), which has been reported in compound heterozygous state in another Dutch family (Ehmke et al, ; Kant et al, ). She presented with retrognathia and cleft palate, and her facial appearance is similar to the Individual 2 reported by Ehmke et al () and the individual reported by Pferdehirt et al (). Individual 2 in this report carries the above mentioned variant c.700T>C, p.(Tyr234His) and the most common variant c.298G>A, p.(Ala100Ser).…”
Section: Discussionsupporting
confidence: 83%
“…The two individuals described here are the first with confirmed TGDS pathogenic variants who present with almost normal hand radiographs and therefore do not show one of the clinical hallmarks of Catel‐Manzke syndrome, that is, Manzke dysostosis (Manzke, ). Until now, nine individuals (including one fetus) with biallelic TGDS pathogenic variants have been reported (Ehmke et al, ; Pferdehirt et al, ; Schoner et al, ). All individuals presented with Pierre‐Robin sequence and hyperphalangy; only in the fetus shortening of the proximal second and third phalangeal bone was detected but no hyperphalangy, which could be due to the early time point of imaging (22nd week of gestation) (Schoner et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the majority of reported cases have had Robin sequence, eight individuals did not have a cleft palate. Of these eight cases without cleft palate, two have had molecularly confirmed pathogenic variants in TGDS (Ehmke et al, ; Kant, Oudshoorn, Gi, Zonderland, & Haeringen, ; Pferdehirt, Jain, Blazo, Lee, & Burrage, ). Thirty‐nine of the 41 reported cases have had bilateral Manzke dysostosis, while in two cases, only one hand was affected (Oh, Kim, Park, Park, & Yang, ; Skinner, Stevenson, & Flannery, ).…”
Section: Introductionmentioning
confidence: 99%